Brak wiedzy koniecznej o małżeństwie jako wada zgody małżeńskiej (kan. 1096 §§ 1-2 KPK) - Dzierżon, Ginter (Ius Matrimoniale, 2011)
The author of the presented article focused on the interpretation of canon can. 1096 §§ 1 -2 CIC. What he pointed out is that canon includes elements essential to knowledge about marriage, necessary to enter into marriage. Raising the issue of the necessity for the contracting parties to obtain knowledge as for the spouse’s own good, the author supported the thesis that this requirement is partially contained in the knowledge of relativity of marital union pointed out by the docrine. As far as future codification is concerned, the author spoke in favor of abolishing the presumption included in canon 1096 § 2 CIC because of the difficulties connected with determining the age og maturity. What he calls for is that in this case reference should be made to the solution codified in Code of Canons of the Eastern Church (ca. 891), in which the legislator did not address the issue leaving it to judges hearing the case to determine the required age of maturity.